ANALISIS FAKTOR LINGKUNGAN DAN KETAHANAN PANGAN DENGAN KEJADIAN STUNTING PADA ANAK USIA SEKOLAH - Yurizal Yurizal; Wilda Sinaga; Yesi Nurmawi (NHM PRESS, 2023)
The potential for a pandemic to trigger an increase in the malnutrition crisis in 2020 is that 132 million people suffer from hunger and 370 million school-age children do not receive adequate food, 47 million children are wasted and 144 million are stunted. The purpose of the study was to analyze environmental factors, maternal characteristics, and household food security with stunting in SD 22/IV and SD 87/IV Jambi City. The design of this study was cross sectional with a sample of 70 children. The sampling was stratified random sampling based on proportional allocation. Data collection techniques using questionnaires, observation sheets and anthropometry. Analysis using Chisquare test. The study found 24.3% stunting, 14.3% inadequate drinking water sources, 44.3% inadequate environmental sanitation, 47.1% low maternal nutrition knowledge and 48.5% low maternal education level, and home food security stairs during the pandemic are not safe 45.7%. There is a relationship between environmental factors, knowledge of maternal nutrition and household food security during the pandemic with the incidence of stunting in school-age children. Environmental factors, knowledge of maternal nutrition and household food security during the Covid-19 pandemic are factors related to the incidence of stunting in school-age children.